Viral vectors for neuronal cell type-specific visualization and manipulations. (August 2020) - Liu, Yuanyuan; Hegarty, Shane; Winter, Carla; Wang, Fan; He, Zhigang
Abstract : Characterizing neuronal cell types demands efficient strategies for specific labeling and manipulation of individual subtypes to dissect their connectivity and functions. Recombinant viral technology offers a powerful toolbox for targeted transgene expression in specific neuronal populations. In order to achieve cell type-specific targeting, exciting progress has been made to: alter viral tropisms, design rational delivery strategies, and drive selective expression patterns with engineered DNA sequences in viral genomes. For the latter case, emerging single-cell genomic analyses provide rich databases. In this review, we will summarize current status, and point out challenges, of using viral vectors for neuronal cell type-specific visualization and manipulations. With concerted efforts, progress will continue to be made toward developing viral vectors for the vast array of neuronal subtypes in the mammalian nervous system.